2013
DOI: 10.5090/kjtcs.2013.46.6.439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Radiocephalic Fistula Using Side-to-side Anastomosis with Distal Cephalic Vein Ligation

Abstract: BackgroundThe surgically created arteriovenous fistula has recently been recommended as the best available angioaccess for hemodialysis. Therefore, in this study, we carried out a clinical analysis on surgical procedures in the ligation and division of a distal vein to achieve similar effects as those of vein end-to-arterial side after side-to-side anastomosis.MethodsWe retrospectively reviewed the clinical data of 113 patients who came for an outpatient clinic follow-up to the department of internal medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…[7] When we consider early complication rates we saw that high thrombosis rates especially in radiocephalic location were associated with anatomical limitations of surgery in this area where also most of bleeding and hematoma formations occurred. Radiocephalic location was announced in the literature as most common location for thrombosis in early period [8] as well. Radiocephalic location being most common choice of surgeons for fistula creation causes reasonable high rates for complications like hematoma and bleeding so that induces early thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7] When we consider early complication rates we saw that high thrombosis rates especially in radiocephalic location were associated with anatomical limitations of surgery in this area where also most of bleeding and hematoma formations occurred. Radiocephalic location was announced in the literature as most common location for thrombosis in early period [8] as well. Radiocephalic location being most common choice of surgeons for fistula creation causes reasonable high rates for complications like hematoma and bleeding so that induces early thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups perform SS anastomosis technique but with distal vein ligation (SE functionality), not included in this study. 3 Referring to the elbow, SS anastomosis (usually brachiobasilic) can provide higher flow with more matured distal usable veins, 4 avoiding proximal basilic vein superficialization, reaching shorter time to access puncture, less operative complications and expected better patency, compared to SE brachiobasilic fistula with vein superficialization. 5 However, with SS anastomosis there is a higher risk of AVF-induced ischemia, vein approximation, and mobilization is more difficult, and there is a higher risk of distal venous hypertension, without clear published differences in patency.…”
Section: Introductionmentioning
confidence: 99%
“…Some groups perform SS anastomosis technique but with distal vein ligation (SE functionality), not included in this study. 3…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have reported different incidences of complications among these types of AVF. End-to-end anastomosis has the lowest fistula maturation rate, and arterial end-to-venous side fistula has the Risk of venous hypertension [4] . Vein end-to-arterial side anastomosis (ETS) has the highest proximal venous flow and a relatively low risk of venous hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Vein end-to-arterial side anastomosis (ETS) has the highest proximal venous flow and a relatively low risk of venous hypertension. Side-to-side (STS) anastomosis is the most commonly used technique and has been described to be the easiest www.jmscr.igmpublication.org Impact Factor (SJIF): 6.379 Index Copernicus Value: 79.54 ISSN (e)-2347-176x ISSN (p) 2455-0450 DOI: https://dx.doi.org/10.18535/jmscr/v6i11.02 to construct technically [4] , however, this procedure has the risk of venous hypertension and carries a high risk of steal syndrome [5] .…”
Section: Introductionmentioning
confidence: 99%